2009
DOI: 10.1143/jjap.48.020219
|View full text |Cite
|
Sign up to set email alerts
|

Continuum-Based Bridging Model of Nanoscale Thin Film Considering Surface Effects

Abstract: We report the optical design of a solid immersion mirror (SIM) incorporated with a flying slider -called a SIM slider -for a near-field recording (NFR) system, its fabrication process, and optical evaluation. To achieve diffraction-limited performance $=14 (rms), a two-step glass-molding process was employed to fabricate the SIM. The numerical aperture of the SIM slider was 1.29. The rms value of the total wavefront aberration was 0:0679. The fabricated SIM slider achieves the optical performance estimated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…© 2010 American Institute of Physics. The elastic prop-erties and coefficient of thermal expansion of copper thin films have been investigated by Cho et al, 16 and we determined that a thin film can be stiffer or more flexible with respect to the surface orientation and loading direction due to surface effects. [1][2][3][4][5] For thin film structures with nanometer-range thickness dimensions, the surface-tovolume ratio is very high compared to bulk counterparts.…”
Section: Surface Effects On the Dynamic Behavior Of Nanosized Thin Fimentioning
confidence: 85%
“…© 2010 American Institute of Physics. The elastic prop-erties and coefficient of thermal expansion of copper thin films have been investigated by Cho et al, 16 and we determined that a thin film can be stiffer or more flexible with respect to the surface orientation and loading direction due to surface effects. [1][2][3][4][5] For thin film structures with nanometer-range thickness dimensions, the surface-tovolume ratio is very high compared to bulk counterparts.…”
Section: Surface Effects On the Dynamic Behavior Of Nanosized Thin Fimentioning
confidence: 85%
“…Cho et al [2009] suggested a sequential multiscale method in order to determine initial surface stress and surface Lamé constants using a matching method based on a molecular dynamics (MD) simulation. As an extension of this multiscale model, a finite element analysis including thermomechanical properties was carried out by Choi et al [2010a].…”
Section: Wonbae Kim Seung Yun Rhee and Maenghyo Chomentioning
confidence: 99%
“…For this reason, solid crystal surfaces contain excess surface energy and residual surface stress. The surface stress significantly affects the equilibrium state and elastic properties of a nanostructure [Wolf 1991;Cammarata and Sieradzki 1989;Streitz et al 1994]. Streitz et al [1994] introduced a surface stress model and calculated the equilibrium biaxial strain and biaxial modulus for an axis-symmetric thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cho et al [2009] proposed a continuum-based bridging model for a nanofilm using the surface elasticity model by Gurtin and Murdoch [1975;. Cho et al [2009] suggested a sequential multiscale method in order to determine initial surface stress and surface Lamé constants using a matching method based on a molecular dynamics (MD) simulation. As an extension of this multiscale model, a finite element analysis including thermomechanical properties was carried out by Choi et al [2010a].…”
Section: Introductionmentioning
confidence: 99%